DORMANCY DYNAMICS OF ‘FUYU’ PERSIMMON TREE BUDS IN A REGION OF LOW CHILL OCCURRENCE - CARVALHO, Ruy Inacio Neiva de; BIASI, Luiz Antonio; ZANETTE, Flávio; RENDOKE, José Carlos; SANTOS, Jean Magnus; PEREIRA, Gabriely Pinto (Scientia Agraria, 2010)
The objective of this work was to evaluate the dormancy dynamic of persimmon tree buds 'Fuyu' during autumn and winter in a region of low chill occurence. The stems were collected in an orchard in Fazenda Rio Grande, Parana State, Brazil, in 10 dates in the period from april to august of 2007 and 2008. In the last date, an addicional group of stems was collected and mainteined in a refrigerator (4 a 7 °C) by 672 h. The evaluation of dormancy was observed by the biological test of single node cuttings under controlled conditions (25 °C and photoperiod of 16 h) by the parameters average time for budburst (TMB), final rate of budburst (TF), average time for open leaves to appear (TMFA), rate of vigorous budburst (TBV) and velocity of budburst (VB). The entirely randomized experimental design was used with 11 treatments and four replications. The two years were analysed individually. The more intense endodormancy period of persimmon tree buds occure from mid may to early june in a region of low chill occurrence.